Medizinische Ontologien: das Ende des MeSH / Medical ontologies: the end of MeSH - Cazan, Constantin (GMS Medizin – Bibliothek – Information, 2006)
Since the beginning of information technology the complexicity of medical questions and medical information management is an important topic which challenges computer scientists.In the eighties of last century artificial intelligence went awry. Though some core ideas of AI have brought up fruitful results. After all congruent development in a number of different scientific disciplines and the exponential development in computer hardware could meet the high requirements in medical information search. In 2000 Tim Berners-Lee's programmatic request for a Semantic Web gained the ontology topic broader attention. Already 20 years ago NLM started to develop the Unified Medical Language System (UMLS). So in medicine (PubMed) ontology integrated into a semantic net is in operation. Hence it is high time for medical librarians and documentalists to get into this topic although it is covered by a smoke screen of terminology from IT. Ontologies can be understood as tools for classification. So essential contributions from library and documentation science could be expected. This paper should open an entrance to the topic. It will explain fundamental elements of UMLS and includes an annotated list of literature for further studies.